Does non-activated platelet-rich plasma (PRP) enhance fat graft outcome? An assessment with 3D CT-scan in mice. Issue 4 (April 2019) - Atashi, Fatemeh; André-Lévigne, Dominik; Colin, Didier J.; Germain, Stéphane; Pittet-Cuénod, Brigitte; Modarressi, Ali
Summary: Background: The adjunction of autologous platelet-rich plasma (PRP) is emerging as a promising approach to enhance the long-term survival of fat grafting, but there are still insufficient data on its efficacy. The aim of this in vivo study was to assess the effect of the addition of non-activated PRP on fat graft outcome. Methods: Human adipose tissue mixed with 20% of non-activated PRP was injected under the scalp skin of nude Balb/cAnNRj mice and compared to grafted fat mixed with 20% of saline. The fat graft volume was analyzed by a computed tomography scan until day 90 and immunohistochemistry was then performed to assess adipocyte viability and graft revascularization. Results: At day 90, the volume of fat graft was not enhanced by PRP compared to the saline control group. However, immunohistochemistry showed that PRP significantly increased the fat graft area occupied by intact adipocytes compared to the saline group (72.66% vs. 60.78%, respectively; p < 0.05). Vascularity was also significantly higher in the PRP group compared to the control group (6695 vs. 4244 CD31 + cells/µm 2, respectively; p < 0.05). Conclusion: The adjunction of non-activated-PRP to fat grafts significantly increased adipocyte viability and tissue vascularity. However, in contrast to other studies adding activated-PRP, non-activated-PRP did not increase residual fat graft volume until day 90. Further studies are therefore needed to understand whether PRP has a positive effect on fat graft volume. As 3D computed tomography scan is a reproducible and precise technique, it should be used to analyze fat graft volume changes over time.